Predictors of expert providers' familiarity with intervention practices for school- and transition-age youth with autism spectrum disorder. (February 2023) - Cooper, Chelsea M; Rosen, Tamara; Kim, Hyunsik; Eaton, Nicholas R; Cohn, Elizabeth; Drahota, Amy; Moskowitz, Lauren J; ,; Lerner, Matthew D; Kerns, Connor M
Understanding the types of intervention practices familiar to transdisciplinary autism spectrum disorder providers may be critical to characterize and optimize "usual care" for common clinical concerns (e.g. internalizing, externalizing, and social challenges) among school- and transition-age autistic youth. We assessed if there is an underlying factor structure to expert providers' familiarity with such practices, and if characteristics of experts (discipline, years' experience, and school setting) and/or their clients (age and intellectual disability) predicted these factors. Fifty-three expert providers rated their familiarity with 55 practices via an online Delphi poll. Exploratory structural equation modeling identified latent factors of familiarity, which were regressed onto provider and client variables to identify predictors. Four factors emerged: two approaches (cognitive and behavioral) and two strategies (engagement and accessibility). Cognitive approaches were associated with practicing outside school settings and treating clients without intellectual disability, behavioral approaches with practicing in schools and the disciplines of clinical psychology and behavior analysis, engagement strategies with practicing outside school settings, and accessibility strategies with more years in practice. Findings suggest expert transdisciplinary autism spectrum disorder providers are familiar with many of the same approaches and that differences in knowledge are predicted by their discipline, treatment setting, experience, and work with youth with intellectual disabilities. Lay abstract: School-age children, adolescents, and young adults with autism spectrum disorder encounter many different types of providers in their pursuit of treatment for anxiety, behavior problems, and social difficulties. These providers may all be familiar with different types of intervention practices. However, research has not yet investigated patterns in expert providers' familiarity with different practices nor how these patterns are related to the characteristics of providers (years in practice, academic discipline, setting) and the youth (age and intellectual disability) they typically support. A panel of 53 expert transdisciplinary providers rated their familiarity with 55 intervention practices (derived from research and expert nominations) via an online Delphi poll. Advanced statistical methods were used to identify types of intervention practices with which providers were familiar, which included two approaches (cognitive and behavioral) and two strategies (engagement and accessibility). Providers who practiced outside a school setting or treated clients without intellectual disability were more familiar with cognitive approaches. Clinical psychologists, behavior analysts, and school-based providers were more familiar with behavioral approaches. Providers practicing outside school settings were also more familiar with engagement strategies, and providers with more years in practice were more familiar with accessibility strategies. These results may help families and researchers to better anticipate how services may vary depending on the types of autism spectrum disorder providers seen and work to reduce disparities in care that may result.